Europe's India : words, people, empires, 1500-1800 - Subrahmanyam, Sanjay (Cambridge, Harvard University Press, 2017)
Europe's India tracks the changing place of India in the European imagination over three centuries, by looking closely at a varied cast of actors and sites of interaction, from ports and coastal enclaves to inland courts. The opening of the Cape Route by Vasco da Gama in 1498 created a new set of conditions for dealings between Europe and India (and Asia more generally). In the decades that followed, many different Europeans - traders, military men, missionaries and others - came to India, and produced a set of images regarding the sub-continent that left a deep imprint on the European imagination. Initially, the Europeans were relatively minor actors on the fringes of India, but over time they came to occupy a situation of power, especially after about 1750. The particular strength of this book is its close examination of a number of individual agents, acting both within the European empires, and at their fringes. Though the central axis is that between Europe and India, this is equally a larger exercise in a global and connected history of the early modern world.--
Introduction: Before and beyond "orientalism" -- On the Indo-Portuguese moment -- The question of "Indian religion" -- Of co-production: the case of James Fraser, 1730-50 -- The transition to colonial knowledge -- By way of conclusion: India's Europe
Includes bibliographical references and index
Keywords: Europeans -- Attitudes -- History; Orientalism -- History; Europe -- Civilization -- Indic influences; India -- Civilization -- European influences; India -- Foreign public opinion, European -- History